Carcinogenic Liver Fluke Secretes Extracellular Vesicles That Promote Cholangiocytes to Adopt a Tumorigenic Phenotype - Chaiyadet, Sujittra (J Infect Dis, 2015)
Background. Throughout Asia, there is an unprecedented link between cholangiocarcinoma and infection with the liver fluke Opisthorchis viverrini. Multiple processes, including chronic inflammation and secretion of parasite proteins into the biliary epithelium, drive infection toward cancer. Until now, the mechanism and effects of parasite protein entry into cholangiocytes was unknown. Methods. Various microscopy techniques were used to identify O. viverrini extracellular vesicles (EVs) and their internalization by human cholangiocytes. Using mass spectrometry we characterized the EV proteome and associated changes in cholangiocytes after EV uptake, and we detected EV proteins in bile of infected hamsters and humans. Cholangiocyte proliferation and interleukin 6 (IL-6) secretion was measured to assess the impact of EV internalization. Results. EVs were identified in fluke culture medium and bile specimens from infected hosts. EVs internalized by cholangiocytes drove cell proliferation and IL-6 secretion and induced changes in protein expression associated with endocytosis, wound repair, and cancer. Antibodies to an O. viverrini tetraspanin blocked EV uptake and IL-6 secretion by cholangiocytes. Conclusions. This is the first time that EVs from a multicellular pathogen have been identified in host tissues. Our findings imply a role for O. viverrini EVs in pathogenesis and highlight an approach to vaccine development for this infectious cancer.